Synergistic Antithrombotic Properties of G4120, a RGD-Containing Synthetic Peptide, and Argatroban, a Synthetic Thrombin Inhibitor, in a Hamster Femoral Vein Platelet-Rich Thrombosis Model - Imura, Yoshimi; Stassen, Jean-Marie; Vreys, Ingrid; Lesaffre, Emmanuel; Gold, Herman K; Collen, Désiré (Thrombosis and Haemostasis, 1992)
The synergistic antithrombotic properties of G4120, a synthetic Arg-Gly-Asp (RGD) containing peptide which strongly inhibits platelet aggregation, and of Argatroban, a synthetic thrombin inhibitor, were examined in a reproducible quantitative hamster femoral vein platelet-rich mural thrombosis model. Bolus injections of G4120 and Argatroban inhibit thrombus formation in a dose-dependent way; 50% inhibition (ID50) is obtained with 11 µg/kg G4120 and with 2 mg/kg Argatroban. Combined bolus injections of 3 µg/kg G4120 with 0.5, 0.75 or 1 mg/kg Argatroban and of 1 mg/kg Argatroban with 1.5 or 3 µg/kg G4120 caused linear dose-dependent inhibition of thrombus formation, whereas 3 µg/kg G4120 or 1 mg/kg Argatroban alone had very little effect (<20% inhibition). ID50 was obtained with the combination of 3 µg/kg G4120 and 0.5 mg/kg Argatroban, corresponding to an equi-effective fractional combination of 0.62 with a 95% confidence interval of 0.50 to 0.74. Alternatively the ID50 was obtained with the combination of 1 mg/kg Argatroban and 1.3 µg/kg G4120, corresponding to an equi-effective fractional combination of 0.52 with a 95% confidence interval of 0.18 to 0.86. In both instances these results are indicative of a significant synergistic interaction. Bolus injection of 10 mg/kg aspirin, 100 U/kg heparin or the combination did not inhibit thrombus formation.The synergistic effect of the combination of platelet inhibiting RGD-peptides and synthetic thrombin inhibitors could be useful in the prevention of arterial occlusion with platelet-rich thrombus in patients with ischemic heart disease following thrombolytic therapy or angioplasty, although this combination is not expected to reverse platelet thrombus formation.